Hypertension in Loa Raya Village: An Analysis of Its Associated RiskFactors - Kharisma Khaerunissa Evan; Puja Nur Wahidah; Siti Maysarah; Dwi Nur Faradiana; Nirgandhi Naib Prabawansyah; Lies Permana (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Hypertension represents one of the leading causes of morbidity and mortality in Indonesia and serves as a major contributor to cardiovascular diseases and stroke. Its prevalence continues to rise nationwide, and in Loa Raya Village, hypertension has been recognized as a significant public health concern, affecting 53% of the adult population. Despite this high prevalence, the underlying factors contributing to hypertension in this community remain insufficiently understood. Objective : This study aims to identify and analyze the factors associated with the occurrence of hypertension among residents of Loa Raya Village. The research focuses on examining demographic and lifestyle-related variables that may contribute to increased blood pressure within the community. This study employed a descriptive survey with a cross-sectional design conducted from June 18 to 20, 2025, in RT 1 and RT 2 of Loa Raya Village. A total of 64 household representatives aged between 27 and 78 years participated as respondents. Data were collected using a structured questionnaire and analyzed using the Chi-square (χ²) test to determine the relationship between independent variables and hypertension status. The Chi-square test showed that age (p = 0.640) and gender (p = 0.215) had no significant association with hypertension status among residents of Loa Raya Village. In contrast, smoking behavior (p = 0.011) and engaging in physical activity for at least 30 minutes per day (p = 0.048) demonstrated a significant association with hypertension status. These indicate that smoking and insufficient physical activity are factors associated with a higher incidence of hypertension. Conclusion/Lesson Learned : Smoking behavior and insufficient physical activity were found to be significantly associated with the prevalence of hypertension in Loa Raya Village. In contrast, age and gender showed no significant association with hypertension status, indicated that lifestyle-related factors play a more substantial role in influencing blood pressure regulation within this community.